How the study on Jane Addams work at Hull House brings new potential for international adult education discussions? - Agnieszka Naumiuk (Adult Education Research Conference, 2023)
The discussion ponts will be raised around the international research on Jane Addams practice as social educator and a discovery of adult education through social activism and empathetic knowledge use.
Keywords: Jane Addams; empathetic knowledge; activists; international discussions